Pengaruh Brand Image, Green Marketing Strategy Dan Emotional Desire Terhadap Keputusan Pembelian Produk Kopi Studio 24 - Febryansyah, Dany; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The café business in Indonesia is rapidly growing and holds significant potential despite intense competition, due to the increasing interest in coffee. This study aims to examine and analyze the influence of brand image, green marketing strategy, and emotional desire on purchasing decisions for Kopi Studio 24 products. The research approach used is quantitative, with data collection through questionnaires. The population in this study consists of consumers who have visited Kopi Studio 24 Sigura-Gura. The sample was calculated using the Malhotra formula, resulting in 70 respondents selected through purposive sampling. The data analysis methods include validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple regression analysis, F-test, t-test, and coefficient of determination. Partially, brand image, green marketing strategy, and emotional desire have a positive and significant impact on purchasing decisions for Kopi Studio 24 products. The contribution of the independent variables to the dependent variable is 75.4%, while the remaining 24.6% is influenced by other variables outside the research model. Keywords: Brand Image, Green Marketing Strategy, Emotional Desire,Purchasing Decisions, Kopi Studio 24